Upaya Guru Kelas dalam Menanamkan Kedisiplinan Siswa Kelas II di SDN 139 Palembang - Riska Amanda; Magdad Hatim; Nyiayu Fahriza Fuadiah (Lembaga Pengembangan Kinerja Dosen, 2024)
Efforts of classroom teachers in instilling self-discipline and social discipline in grade II students at SDN 139 Palembang? The purpose of this study is to find out the efforts of classroom teachers in instilling self-discipline and social discipline in grade II students at SDN 139 Palembang. The method used in this study is a qualitative method, with a descriptive research form. The data collection techniques in the study used questionnaire, interview, and documentation techniques. The Data Validity Techniques used in this study are Source Triangulation, Source Triangulation, Time Triangulation. The data analysis techniques used are Data Reduction, Data Presentation, Data Presentation. Based on research in the field, it can be known that the impact of teachers' efforts in instilling discipline that has been implemented at SD N 139 Palembang has a good effect on student discipline such as wearing complete uniform attributes, departing on time and orderly following the bender ceremony It would be good for the principal and teachers to set an example and give sanctions to students who violate school rules to train the discipline of SD N 139 Palembang students.